Evaluasi Pengalaman Pengguna Pada Aplikasi Mobile E-Commerce Di Indonesia Dengan Menggunakan UX Honeycomb - Salma Mutiasanti; Mahardeka Tri Ananta; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-commerce application is a mobile application that allows users to fulfill their needs without having to physically buy in the store. Some of the main issues of e-commerce applications which become our interest are about transactional security, application navigation, and how good the content or images represent the products being sold. The purposes of this study is to know the values proposed by the stakeholders. The concept which was used, is user experience honeycomb, which contains of seven aspects: accessible, credible, desireable, findable, usable, useful and valuable. Methodology that was used in this study, is by analyzing values proposed observed from vision and mission, slogan, official website, and advertisements of the e-commerce. Based on the result of our proposed values analysis, it is reported that Bukalapak, Lazada, Tokopedia, Zalora, and Matahari Mall possessing all values in ux honeycomb.